Pengaruh Fear Of Missing Out (FoMO) Terhadap Pola Perilaku Mahasiswa Sebagai Pengguna Media Sosial Di Wilayah Universitas Jember (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
The development of technology in the era of modernization creates risks on the rise of social media use. The high number of social media use raises concerns about the consequences of problems that arise, especially related to social media dependence. This dependence makes them feel to always be connected to other activities in social media, which then creates anxiety fear of being left behind by news or trends. This phenomenon is referred to as FOMO (Fear of Missing Out). This sociological research aims to identify the FOMO phenomenon as a result of social media dependence among Jember regional students. Based on interviews and data analysis, this research explores the extent to which Fomo affects the behavior of the use of social media students of Jember University. In addition, this research also identifies the risks and consequences of the dependence of social media that arise due to FOMO. The results of research on a number of Jember University students show that students who experience FOMO tend to have a higher degree of dependence on social media.